Corporate governance moderate the effect of CSR on financial performance - Suryana, I Putu; Sedana, Ida Bagus Panji (International research journal of management, IT and social sciences, 2021)
The purpose of this study was to obtain empirical evidence regarding the effect of CSR (CSR) on the financial performance of companies with corporate governance as a moderating variable (study on the consumer goods industry on the Indonesia Stock Exchange in 2017-2019). The research sample was determined using a non-probability sampling method with a purposive sampling technique. The data used in this study is secondary data obtained from the annual report of consumer goods industry companies on the Indonesia Stock Exchange for the period 2017 - 2019. The data analysis technique uses moderated regression analysis. The results of this study indicate that CSR has a positive and significant effect on financial performance and the board size of directors, independent directors and gender diversity of the board of directors strengthens the influence of CSR on financial performance.